DRAG FORCES TEST FOR LOW SUBSONIC SMALL-SCALE OPEN-CIRCUIT WIND TUNNEL - Nur Faraihan Zulkefli, Muhammad Al-‘Azam Abd Aziz, Nurhayati Mohd Nur (International Journal of Advanced Science and Technology, 2020)
The small-scale open-circuit wind tunnel has been constructed using CATIA software. The drag coefficient performed at velocity 2.5m/s, 5m/s and 10m/s correspond to Reynolds number 25 000, 50 000 and 100 000 in low subsonic flow. The NACA 0018 drag coefficient was measured using mini weighting scale. The angle of attack was set at 0 deg, 5 deg and10 deg. The drag coefficient from small-scale open-circuit wind tunnel and calibrated wind tunnel were validated with Airfoil Tools data. Both drag coefficients provides from small-scale open-circuit wind tunnel and calibrated wind tunnel give less than 15% difference for all Reynolds number. This experimental works for Reynolds number 50 000 and 100 000 also provides less than 30% drag coefficient compared to data from Airfoil Tools. The result shows a good agreement for all cases.